Effects of Anterior Capsulotomy on Decision Making in Patients with Refractory Obsessive–Compulsive Disorder - Zhang, Chencheng; Chen, Yilin; Tian, Shuaiwei; Wang, Tao; Xie, Yile; Jin, Haiyan; Lin, Guozhen; Gong, Hengfen; Zeljic, Kristina; Sun, Bomin; Yang, Tianming; Zhan, Shikun (Frontiers in Psychology, 2017)
Despite various lines of evidence implicating impaired decision-making ability in individuals with obsessive-compulsive disorder (OCD), neuropsychological investigation has generated inconsistent findings. Although the cortico-striato-thalamo-cortical (CSTC) circuitry has been suggested, the involvement of the cortex has not yet been fully demonstrated. Moreover, it is unknown whether surgical intervention on the CSTC circuitry results in a predicted improvement of decision-making ability of OCD. Here we present a study of decision-making based on the Iowa Gambling Task (IGT) to investigate decision making in a large sample of individuals with treatment-resistant OCD with and without anterior capsulotomy (AC). Task performance was evaluated in healthy subjects, individuals with OCD that had not undergone surgery, and postsurgical OCD patients with AC. The latter group was further divided into a short-term postsurgical group and a long-term postsurgical group. We found that the OCD patients without surgery performed significantly worse than the health controls on the IGT. There were no significant differences in decision-making between the presurgical OCD patients and those at the short-term postsurgical follow-up. Decision-making ability of the long-term postsurgical OCD patients was improved to the level comparable to that of health controls. All clinical symptoms (OCD, depression, and anxiety) assessed by psychiatric rating scales were significantly alleviated post-surgically, but exhibited no correlation with their IGT task performance. Our findings provide strong evidence that OCD is linked to impairment in decision-making ability; that impaired CSTC circuitry function is directly involved in the manifestation of OCD; and that AC related improvements in cognitive functions are caused by long-term plasticity in the brain circuitry.